1989
DOI: 10.1111/j.1476-5381.1989.tb14613.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptors on the somatic muscle cells of the parasitic nematode, Ascaris suum: stereoselectivity indicates similarity to a GABAA‐type agonist recognition site

Abstract: 1 The y-aminobutyric acid (GABA) receptors on the somatic muscle cells of Ascaris, which mediate muscle cell hyperpolarization and relaxation, have been characterized by use of intracellular recording techniques. 2 These receptors are like mammalian GABAA-receptors in that the response is mediated by an increase conductance to chloride ions. The GABAA-mimetic, muscimol, has a relative potency of 0.40 + 0.02 (n = 3) compared to GABA. 3 The stereoselectivity of the GABA receptor on Ascaris is identical to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 52 publications
6
52
0
Order By: Relevance
“…These studies are hard to interpret as the pharmacological selectivity of these antagonists in invertebrates appears to be different from their well-established effects in mammalian systems. Indeed, bicuculline blocks invertebrate nicotinic ACh responses (Benson 1988) and in Ascaris suum neither it, nor picrotoxin, block GABA-A like body wall muscle responses (Holden-Dye et al 1989). Therefore, while it seems very likely that GABA is the inhibitory transmitter at the body wall neuromuscular junction of plant parasitic nematodes, there is no direct evidence to confirm this.…”
Section: Amino Acidsmentioning
confidence: 99%
“…These studies are hard to interpret as the pharmacological selectivity of these antagonists in invertebrates appears to be different from their well-established effects in mammalian systems. Indeed, bicuculline blocks invertebrate nicotinic ACh responses (Benson 1988) and in Ascaris suum neither it, nor picrotoxin, block GABA-A like body wall muscle responses (Holden-Dye et al 1989). Therefore, while it seems very likely that GABA is the inhibitory transmitter at the body wall neuromuscular junction of plant parasitic nematodes, there is no direct evidence to confirm this.…”
Section: Amino Acidsmentioning
confidence: 99%
“…This early evidence for the presence of GABA receptors in nematodes was corroborated decades later by Martin, Holden-Dye and colleagues who investigated the somatic muscle GABA receptor in the related nematode Ascaris suum and demonstrated that it exhibited a unique pharmacological profile (Holden-Dye et al 1988, 1989Holden-Dye and Walker 1990;Martin 1980Martin , 1985Martin et al 1991). For instance, while the Ascaris receptor was shown to be activated by many of the classical GABA A receptor agonists such as muscimol and isoguvacine, it was insensitive to sulphonic acid derivatives such as piperidine-4-sulphonic acid and 3-aminopropane sulphonic acid (Holden-Dye et al 1988;Martin 1982).…”
Section: The Origins Of Gaba Receptor Research In Nematodesmentioning
confidence: 79%
“…For instance, while the Ascaris receptor was shown to be activated by many of the classical GABA A receptor agonists such as muscimol and isoguvacine, it was insensitive to sulphonic acid derivatives such as piperidine-4-sulphonic acid and 3-aminopropane sulphonic acid (Holden-Dye et al 1988;Martin 1982). In addition, unlike vertebrate GABA A receptors, the Ascaris receptor was not potentiated by pentobarbitone or flurazepam (Holden-Dye et al 1989). Perhaps most intriguing Box 1 GABA receptor subunit phylogeny Nematode GABA receptor subunit sequences were identified by a blastp search of the Genbank database (NCBI).…”
Section: The Origins Of Gaba Receptor Research In Nematodesmentioning
confidence: 99%
“…In terms of the barbiturates, we can conclude that C. elegans GluCl channels, in common with vertebrate GABA-A-gated chloride channels, have a binding site. Intriguingly, evidence from GABA receptors on Ascaris body wall muscle suggests that these channels are insensitive to barbiturates (Holden-Dye et al 1989). Thus, a nematode glutamategated chloride channel, but not a nematode GABA-gated chloride channel, is sensitive to barbiturates.…”
Section: Discussionmentioning
confidence: 99%